Health Services, Maternal Intrinsic and Socio-Cultural Factors and Perinatal Mortality - Diaz Viera, Andika Alexander; Pellokila, M R; Paun, Rafael (KEMAS: Jurnal Kesehatan Masyarakat, 2017)
This study question was how significant the determination of health services, maternal intrinsic risk factors and socio-cultural factors on perinatal mortality.  Its objective was to construct a model of perinatal mortality pattern by case-control design.  The case population was all mothers with perinatal mortality.  The sample-size was 35 by simple random sampling with case-control ratio of 1:1 (35:35).  The data analysis applied Bivariate using Chi Square Test and Multivariate using Logistic Regression Test.  The Bivariate Analysis Results found the risk-variables on Perinatal Mortality were Birth Attendant (OR=2.1; 1.63-2.7; 95%CI), Health Financing (OR=7.1; 1.82-27.8; 95% CI), Maternal Disease History (OR=8; 2.05-31.16; 95%CI), Perinatal History (OR=6.47; 2.26-18.55; 95%CI) and Custom (OR=2.17; 1.67-2.82; 95%CI).  Multivariat Analysis found three consistent risk variables on Perinatal Mortality i.e.: Health Financing (p=0.016; OR=6.8; 95% CI), Maternal Disease History (p=0.006; OR=8.41; 95%CI) and Perinatal History (p=0.021; OR=4.3; 95%CI). It concluded that the most significant determinant on Perinatal Mortality was Maternal Disease History.